(untitled) (International Journal of Natural Sciences Research, 2022)
Dietary protein in broiler feeds comes mainly from soybean meal and to a lesser extent from animal protein. Nowadays, animal protein is not recommended as a broiler feed ingredient because it is associated with zoonotic diseases such as salmonellosis and soybean is very scarce in Zimbabwe due to low productivity. This shortage is causing an increase in the cost of soybean and making broiler production less viable. Shortage of soybean is forcing animal nutritionists to search for potential alternative sources of protein. Cowpea is the best alternative since it is locally available, cheap and drought tolerant. Cowpea use in broiler feed manufacture is limited because it contains some anti-nutritional factors which reduce protein digestibility and broiler growth performance. The objectives of this paper are to determine the effectiveness of dehulling, roasting and boiling cowpea on nutrient and anti-nutrient content, protein digestibility and broiler performance. The purpose of this review paper is to develop cost effective broiler diets from cowpea. Protein digestibility was measured by using ecxreta analysis through subtracting protein in excreta from protein in feed ingested and broiler weight gains were measured by subtracting final bird weight from previous bird weight. Feed conversion ratio was calculated from dividing weight of total feed eaten by weight gained by the birds.